1987
DOI: 10.1111/j.1550-7408.1987.tb03137.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Acid Phosphatase Activity in Giardia lamblia and Giardia muris Trophozoites1

Abstract: Numerous membrane-bounded vacuoles are found adjacent to the plasma membrane of the pathogenic protozoan Giardia lamblia. The function of these vacuoles has been discussed by several authors. Approximately 100-400 nm in diameter with a core of low electron density, they have been suggested to be mitochondria, mucocysts, lysosomes, and endocytotic vacuoles. Enzyme cytochemical localization for acid phosphatase activity using cerium as a capturing agent demonstrates reaction product in these vacuoles as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…It has been postulated that proteases may be involved in this process. Several studies have demonstrated protease activity in total extracts of Giardia trophozoites or in parasite vacuoles (Feely & Dyer 1987, Hare et al 1989) including the Portland 1 (P1) strain cultured in vitro, with the predominance of cysteine, serine, and aspartic protease activities (Williams & Coombs 1995). It has also been shown that cysteine proteases of P1 strain degraded protein substrates such as gelatin, collagen, albumin, and azocasein while serine proteases were mainly active against haemoglobin (Coradi & Guimarães 2006).…”
mentioning
confidence: 99%
“…It has been postulated that proteases may be involved in this process. Several studies have demonstrated protease activity in total extracts of Giardia trophozoites or in parasite vacuoles (Feely & Dyer 1987, Hare et al 1989) including the Portland 1 (P1) strain cultured in vitro, with the predominance of cysteine, serine, and aspartic protease activities (Williams & Coombs 1995). It has also been shown that cysteine proteases of P1 strain degraded protein substrates such as gelatin, collagen, albumin, and azocasein while serine proteases were mainly active against haemoglobin (Coradi & Guimarães 2006).…”
mentioning
confidence: 99%
“…They are acidic, as shown by the uptake of acridine orange and the lysosomal markers Lyso-sensor and Lysotracker (Lanfredi-Rangel et al, 1998;Touz et al, 2002b;Touz et al, 2003). The first description of hydrolase activity in the PVs came from studies in which acid phosphatase activity was tested, showing a cytochemical localization in these vacuoles as well as in the ER and nuclear envelope cisternae (Feely and Dyer, 1987). The presence of hydrolase activities in the PVs was also proved for cysteine proteases and RNases, demonstrating their lysosomal characteristics (Lindmark, 1988;Ward et al, 1997;Touz et al, 2002b).…”
Section: The Endosomal/lysosomal System Of Giardiamentioning
confidence: 98%
“…A family of three cysteine protease genes (CP1, CP2, and CP3) has been shown to encode members of the cathepsin B subgroup of the peptidase family C1 (Ward et al, 1997), and soluble CP2 has been found in PVs and ER of trophozoites (Ward et al, 1997;Abodeely et al, 2009a). Also, AcPh activity has been examined cytochemically, revealing communication of the PVs with the ER (Feely and Dyer, 1987;Lanfredi-Rangel et al, 1998;de Souza et al, 2004). Unlike AcPh in other eukaryotes, including protozoa, Giardia AcPh is a soluble protein that is transported from the ER-exit site to the PVs via AP-1 (Touz et al, 2004).…”
Section: Lysosomal Proteinsmentioning
confidence: 99%
“…2 presents the results of a differential centrifugation performed on a Giardia homogenate. The activity of cathepsin C was measured in the different fractions and its distribution compared to that of acid phosphatase, an enzyme known to be located in Giardia peripheral vesicles (Feely and Dyer, 1987;Lindmark, 1988;Feely et al, 1991). The distributions were very similar, both being enriched in the L fraction.…”
Section: Subcellular Localization Of Giardia Cathepsin Cmentioning
confidence: 99%
“…These have an acidic content as seen by their staining with acridin orange (Feely et al, 1991). Acid phosphatase has been cytochemically localized in these structures (Feely and Dyer, 1987). Biochemical methods have also revealed the presence of some acid hydrolases in these organelles.…”
Section: Introductionmentioning
confidence: 98%